The Genomic Signature of Demographic Decline in a Long‐Distance Migrant in a Range‐Extreme Population - George Day; Thomas Bolderstone; Greg J. Conway; Tony Cross; Tony Davis; Matilda Dolan; Mervyn Greening; Colin Neale; Ian Nicholson; Kim Nicholson; Ann Ward; Nik Ward; et al. (Molecular Ecology, 2025)
Migratory birds are inherently vagile, a strategy that may reduce the impacts of habitat loss and fragmentation on genetic diversity. However, specialist resource requirements and range‐edge distribution can counteract these benefits. The European nightjar ( Caprimulgus europaeus ) is a long‐distance migratory bird and resource specialist. Like other long‐distance migrants, nightjar populations have declined across the British Isles and Northwestern Europe over the past century. With this decline well documented in the British Isles, there is a need to quantify its genetic impacts. We applied full genome resequencing to 60 historic (1841–1980) and 36 contemporary British nightjars. Nightjars exhibited a statistically significant 34.8% loss in heterozygosity and an increase in inbreeding over the last ~180 years, showing a departure from panmixia towards weak spatial structure in the modern population. Such fine‐scale structuring in migratory birds is rare. Our results provide a case study of fragmentation's impact on a species with specialist resource requirements at its range limit. Similar demographic declines in nightjars and other long‐distance migrants across Northern and Western Europe suggest that genetic patterns seen in the British population may reflect those in other nightjar populations and European avifauna. Whilst our results indicate no immediate conservation concern, they depict a trajectory of declining genetic diversity, increasing inbreeding and genetic structure, potentially shared with other migratory species. Our study highlights the value of applying spatiotemporal population genetics analysis to migratory birds, despite their inherent vagility.

Pandemic gardening: A narrative review, vignettes and implications for future research - Jonathan Kingsley; Kelly Donati; Jill Litt; Naomi Shimpo; Chris Blythe; Jan Vávra; Silvio Caputo; Paul Milbourne; Lucy O. Diekmann; Nick Rose; Runrid Fox-Kämper; Agnes van den Berg; et al. (Urban Forestry & Urban Greening, 2023)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)